1979
DOI: 10.1111/j.1365-2125.1979.tb04770.x
|View full text |Cite
|
Sign up to set email alerts
|

Labetalol in severe and resistant hypertension.

Abstract: 1 The efficacy of labetalol in the treatment of severe hypertension (diastolic > 115 mm Hg) was studied retrospectively. Ten patients were followed for more than 6 months. At 6 months, eight were well controlled and the mean dose in those was 975 mg daily. Four of these were receiving labetalol alone; two were on labetalol and diuretic only. 2 Three patients were resistant to doses to 1600, 1800 and 2400 mg daily respectively; two of these were controlled with increased doses of vasodilator drugs. In two cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Long term studies of renal function in hypertensive patients who had pre-existing compromised renal function have shown that labetalol treatment per se does not have any deliterious effect on the underlying renal function (Thompson et al, 1979;Bailey, 1979;Williams, 1979). It can be used alone or together with diuretics (Bailey, 1979), the dose of labetalol required to control BP being reduced due to the additive effect of the diuretic.…”
Section: Emergency Hypertensionmentioning
confidence: 99%
See 2 more Smart Citations
“…Long term studies of renal function in hypertensive patients who had pre-existing compromised renal function have shown that labetalol treatment per se does not have any deliterious effect on the underlying renal function (Thompson et al, 1979;Bailey, 1979;Williams, 1979). It can be used alone or together with diuretics (Bailey, 1979), the dose of labetalol required to control BP being reduced due to the additive effect of the diuretic.…”
Section: Emergency Hypertensionmentioning
confidence: 99%
“…In those patients whose BP is difficult to control or when substitution is required for multiple drug treatments, it is now clear that labetalol may be useful (Williams et al, 1979;Bailey, 1979;New Zealand Hypertension Study Group, 1979). Long term studies of renal function in hypertensive patients who had pre-existing compromised renal function have shown that labetalol treatment per se does not have any deliterious effect on the underlying renal function (Thompson et al, 1979;Bailey, 1979;Williams, 1979).…”
Section: Emergency Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation